A Mixed Methods Evaluation Of A LIS Leadership Programme In South Africa - Hart, Genevieve (Qualitative and Quantitative Methods in Libraries, 2017)
The paper reports on an evaluation of the three-year leadership programme of the Centre for African Library Leadership (CALL).  Six twoweek  Leadership Academies were run by the Centre from July 2009 to April 2012, with 20 delegates per course; these were followed by three one-week Train-the-Trainer courses. The goal was to develop leadership qualities in current and future library managers – amid concern over the challenges confronting a new generation of LIS leaders.  The paper focuses on the methodology rather than on the findings – demonstrating the benefits of triangulating the questionnaire data with the follow-up focus group interviews. The debates and discussions within the focus groups lent support to the survey findings but offered more nuanced insights.